THE EFFECT OF PRINCIPAL’S LEADERSHIP AND SCHOOL CULTURE ON STUDENT CHARACTER MEDIATED BY GUIDANCE AND COUNSELING SERVICE EFFECTIVENESS AT MTSS AT-TAQWA SETU - Yusriyah, Khaerunnisa; Oktarina, Nina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The prevalence of caracter violations, particularly verbal and physical bullying, remains a critical challenge in Islamic junior high school environments, including MTsS At-Taqwa Setu, where 21 cases were documented within a single semester. This research aimed to analyze the direct effects of the principal's role and school culture on students character, as well as their indirect effects mediated through the effectiveness of guidance and counseling services. Employing a quantitative explanatory design, this study surveyed a sample of 193 active students selected via proportionate stratified random sampling from a total population of 371 students. Data were collected using structured questionnaires using a Likert scale and analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS 4.0). Descriptive findings indicated that the principal’s role, school culture, guidance and counseling effectiveness, and student character were all perceived in the good category. The structural model analysis revealed that the principal's role and school culture both exerted significant positive direct effects on student character and guidance and counseling service effectiveness. Furthermore, guidance and counseling effectiveness significantly and positively influenced student character. Importantly, the results confirmed that guidance and counseling service effectiveness serves as a significant mediating variable that bridges and strengthens the impact of both the principal's role and school culture on student character development.